Quaternary marine ingressions: hydrogeochemical evidence in the semi-confined aquifer of the littoral of the Río de la Plata, Argentina - Santucci, Lucía (2017)
The Quaternary is characterized by the occurrence of significant climate oscillations that led to noticeable sea-level changes. The objective of this work is to determine, on the basis of hydrochemical indicators, the origin of saline water in the semi-confined aquifer and its relationship with the palaeoenvironments in the region of the middle Río de la Plata estuary, Argentina. In order to do so, exploration wells were drilled and the sediments were sampled for mineralogical analysis alongside water samples collected to determine major and minor ions and environmental isotopes. The results obtained show that the Plio-Pleistocene fluvial sands in which the aquifer occurs are mainly composed of grains of quartz, feldspar and mafic minerals. The water chemistry shows Na-Cl facies with a marked increase in salinity towards the Río de la Plata. The δ 18O vs. δ 2H, Br− vs. Cl− and δ 18O vs. Cl− ratios have a clear trend towards seawater. Minor ions, such as Si, Sr, Li, Se, Br and Rb, were the result of the prolonged interaction between the water that occurs in the aquifer and the mineral components of its matrix. The hydrogeochemical data point to the marine origin of the saline water and show that the hydrogeological evolution of the area during the Quaternary is as a result of the sea-level oscillations.